Ethosome-Based Transdermal Drug Delivery: Its Structural Components, Preparation Techniques, and Therapeutic Applications Across Metabolic, Chronic, and Oncological Conditions - Rashed M. Almuqbil; Bandar Aldhubiab (Pharmaceutics)
Transdermal drug delivery systems (TDDSs) provide a non-invasive alternative to oral and parenteral routes, delivering drugs into the bloodstream while avoiding gastrointestinal degradation and first-pass metabolism. Despite benefits like enhanced bioavailability and patient compliance, the stratum corneum limits drug permeation. Ethosomes overcome the stratum corneum barrier with superior flexibility and permeability compared to liposomes. Ethanol disrupts the skin’s lipid bilayer, enabling deep penetration and efficient drug delivery. Ethosomes offer high entrapment efficiency and stability, delivering both hydrophilic and lipophilic drugs. However, challenges like stability optimization and clinical translation persist. This review examines the structural components, preparation methods, and therapeutic applications of ethosomes in metabolic and chronic diseases, including diabetes, cardiovascular diseases, neurodegenerative disorders, arthritis, and cancers. Moreover, it highlights the potential of ethosomes to revolutionize TDDSs for managing chronic and metabolic diseases, providing a foundation for further research and clinical development.